The Effectiveness of a Psychological Guidance Rehabilitative Program Accompanied by EMG Technology for the Adductor Muscles of the Thighs on Muscular Strength and Emotional Arousal in Injured Football Players (Texas Journal of Multidisciplinary Studies, 2026)
The Effectiveness of a Psychological Counseling and Rehabilitation Program Combined with EMG Technique for the Adductor Muscles of the Thighs on Muscle Strength and Emotional Arousal in Injured Football Players